THE COMPARISON OF CONVENTIONAL METAPHOR OF ANGER BETWEEN ENGLISH AND MALAY LANGUAGE AND THE IMPLICATION FOR TEACHING AND LEARNING - Nur Akmaliyah (Universitas Islam Negeri Banda Aceh, 2013)
Metaphor is often defined as a phrase used in an imaginative way to describe, com-prehend and conceive one thing in terms of something else. (Lakoff and Johnson, 1980) They, in addition, note that language, activity and human thought are con-ceptualized in metaphoric way. Furthermore, the metaphorical concept in thought is developed from several correlated experience. (Lakoff, 1992; Kovesces, 2005) For example, as it is explained by Lakoff, people talk about love in the way of talking about journey. Love is conceived in the way of journey is understood. Two lovers are positioned as two persons who are in traveling. Their relationship is the vehicle to gain their love expectations in the same way as destination in a journey. They use journey to conceptualize love and act of love in that way. When they find several difficulties along the way, it means that they have problems in their relationship.